Crude Garlic Extract Effect on the Growth of Mycelia, Germination of Zoospores and Sporangia and Time of Application on the Infection of Phytophthora infestans (Mont.) de Bary of Potato under Controlled Conditions in Ethiopia - Kassa Bekepe; Tharmmasak Sommartya; Vijai Rakvidhyasastra; Narong Singburaudom; Patana Sukprasert; Lemaga Berga (Agriculture and Natural Resources, 2006)
The experiments were carried out at Holetta, Ethiopia, Agricultural Research Center laboratory and green house conditions in 2004 crop season. The effects of 0.5 % 2 %, 4 %, 6 % and 8 % concentrations of crude garlic extract and 0.1% fungicide Dithane M 45 (as positive control) and 0 % concentration (as negative control) on the inhibition of the growth of mycelia, germination of zoospore and sporangia of Phytophthora infestans were studied. In addition, the effect of time of applications of 2 % garlic extract on pathogen infection was tested on potato variety Awash in the greenhouse. Results of these studies provided evidence that all concentrations significantly (p<0.05) inhibited the growth of the mycelia compared to the control and the tested concentrations showed highly significant difference (p<0.001) on percent inhibition and germination of zoospores and sporangia compared to the negative control treatment. The 2 % garlic crude extracts showed curative effect on the development of P. infestans when it was applied at a time and one day before inoculation.